“Estudio de factibilidad para la creación de una empresa dedicada a la promoción e implementación de la técnica del paisajismo en parques y jardines de la ciudad de Quito.” - Ruales Ubilluz, Daniel Jhonatan (2013)
The company create is designed to meet the needs of the changing world and specialize in landscaping offer a service of high quality for customer acceptance. This service will include: Creating artificial environments, design and maintenance of green areas for management consulting aesthetic of gardens, etc.. And consulting services to be offered will be commensurate with the needs, tastes and demands of different customers, to thus be able to obtain satisfaction in them.